Meningkatkan Pengetahuan dan Sikap Ibu Hamil tentang Kepatuhan Konsumsi Tablet Fe melalui Media Visual - Tri Siswati; I Made Alit Gunawan; Savitri Fatikaningtyas (PUINOVAKESMAS, 2021)
Prevention and control of anemia can be started by increasing knowledge and attitudes through various programs, one of which is the development of communication, information, and education (IEC) media. This research to determine the differences in the effectiveness of anemia booklets and leaflets on increasing knowledge about anemia and attitudes in consuming iron tablets in pregnant women. This study was quasi-experimental with a pretest-posttest control group design. Data were collected in March 2020 at the Tempel I Health Center and Kalasan Health Center, Sleman Regency, DIY. Subjects were selected purposively. The booklet intervention group was the Tempel I Public Health Centre and the control group/leaflet intervention group was the Kalasan Public Health Centre with 32 subjects each. Data was collected through a google form after obtaining ethics approval. Data were analyzed by Mann-Whitney Test. Booklet intervention increased the mother's knowledge by 3.1 while leaflet by 2.4 there was no significant difference. Intervention with booklet increased mother's attitude about Fe adherence by 4.7 and leaflet by 1 and there was a significant difference (0.002). Booklets are more effective to increase the knowledge about anemia and the attitude of consuming iron tablets in pregnant women than leaflets.